Nominal Metaphor Aptness: Semantic Features and Degree of Matching between Topic and Vehicle - Sedigheh Vahdat; Omid Khatin Zadeh; Babak Yazdani Fazlabadi (Journal of Modern Research in English Language Studies)
Degree of aptness of the nominal metaphor X is a Y or the extent to which the metaphorical statement expresses its specific non-literal meaning and the nature of relationship between aptness and semantic features of topic (X) and vehicle (Y) is the subject that is addressed in this study. Conducting an experiment in which 35 undergraduate students judged degree of relevancy of 10 semantic features of topic and vehicle of nominal metaphors, the researchers of this study sought to find how aptness of a metaphor is related to various meaning aspects of topic and vehicle. The instrument was a test including 20 nominal metaphors, each one followed by 10 semantic features of topic and vehicle. The participants were required to judge the degree of relevancy of each feature on the basis of a Likert scale ranging from 0 (irrelevant) to 3 (completely relevant). The obtained results suggested that several aspects of meaning might simultaneously be in operation throughout metaphor comprehension. However, these aspects are not at the same level; that is, one meaning aspect plays the dominant role, while others play a secondary role. Taking Glucksberg’s class-inclusion view of metaphor comprehension and Gentner’s structure-mapping view and based on the results obtained in the experiment, this article presents a model according to which degree of interpretability and aptness of a nominal metaphor is determined by degree of relevancy of a specific meaning aspect of vehicle.